Changes in Vascular Anatomy following Reconstructive Surgery: An in vivo Angiographic Demonstration of the Delay Phenomenon and Venous Recanalization - Rozen, Warren Matthew; Whitaker, Iain S.; Ashton, Mark W.; Grinsell, Damien (Journal of Reconstructive Microsurgery, 2012)
Background Although a surgical insult may substantially alter local vascular anatomy within tissues, studies that have clearly demonstrated these changes as being dynamic phenomena have not been widely reported. The current study aimed to explore the changes in abdominal wall vasculature after a surgical insult.Methods The arterial and venous anatomy of both the deep and superficial epigastric systems of the abdominal wall were explored with computed tomographic angiography (CTA) performed before and after bilateral removal of both bilateral deep and superficial inferior epigastric systems.Results Several unique anatomic findings were evident, with dilatation of both deep superior epigastric arteries and recanalization of the superficial inferior epigastric veins across the surgical scar, despite previous surgical division.Conclusion The current study demonstrated that there are changes in both major and minor axial vessels and in both the arterial and venous systems after surgical insult. CTA may be of value in identifying these changes prior to surgery utilizing local vasculature.
Keywords: perforator flap; DIEA perforator flap; computed tomographic angiography; breast reconstruction; preoperative imaging